2015
DOI: 10.1212/wnl.0000000000001815
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and cognitive decline in a French cohort of patients infected with HIV-1

Abstract: Objective: We investigated the relationship of diabetes and prediabetes with cognitive performances, assessed through raw test and z scores and according to neurocognitive impairment (NCI) classification in a cohort of individuals infected with HIV. Methods:The ANRS CO3 Aquitaine cohort is a prospective hospital-based cohort of HIV-1-infected patients under routine clinical management in 6 public hospitals in southwestern France. Between 2007 and 2009, an ancillary study consisted of a neuropsychological batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
(36 reference statements)
1
17
0
1
Order By: Relevance
“…12,13 This has crucial implications for the interpretation of longitudinal studies in which the risk of change from ANI to MND is measured, such as the United States CHARTER cohort, 39 the Canadian OHTN Cohort, 6 and the French Aquitaine cohort. 40 For example, in the Ottawa cohort, depression was a major risk factor for change from ANI to MND. 6 Because self-reported functional impairment is associated with depression, change from ANI to MND does not always indicate decline in neurocognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 This has crucial implications for the interpretation of longitudinal studies in which the risk of change from ANI to MND is measured, such as the United States CHARTER cohort, 39 the Canadian OHTN Cohort, 6 and the French Aquitaine cohort. 40 For example, in the Ottawa cohort, depression was a major risk factor for change from ANI to MND. 6 Because self-reported functional impairment is associated with depression, change from ANI to MND does not always indicate decline in neurocognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…30 Each cognitive test was converted to an age-, sex-, and education-standardized Z-score using normative mean values and SD. Normative data for the computerized tests were provided by Cogstate from Europe, United States of America, South East Asia, and Australia/New Zealand, frequencymatched for age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), and 51+ years; minimum cell size n = 145), sex (157 female, 377 male), and education (university/further education, n = 243, or secondary school, n = 291). The normative population excluded individuals with clinical or functional impediments to test performance, and subsets of these data had been used previously to measure cognitive function in HIV+ adults.…”
Section: Cognitive Testingmentioning
confidence: 99%
“…[47] Diabetes with its known accelerated vascular disease is associated with earlier cognitive dysfunction. [48,49] Cohort studies continue to find substantial impact of cardiovascular associated factors affecting cognition, suggesting that this will be one of best areas of concentration to decrease cognitive impairment. [4,50]…”
Section: Biomarkers and Handmentioning
confidence: 99%
“…18 Diabetes has also been linked to greater cognitive decline a French cohort of HIV patients. 19 Our previous study has shown that CIMT is linked to protease inhibitor based ART regiemes. 20 Previous studies have shown that age, especially > 50 years, increases risk of HAND.…”
Section: Discussionmentioning
confidence: 97%